An overview on Lithium-ion batteries recycling processes. Issue 3 (April 2021) - Hu, Qiushi; Xu, Linghong
Abstract: In the last few decades, well-developed lithium-ion batteries (LIB) with high capacity showed great performance in electric vehicles. However, efforts must be made in the field of LIB recycling to reduce the negative effects caused by spent LIB on the environment. The processes for lithium-ion batteries recycling are presented through three different portions includeing pre-treatment, secondary treatment and further treatment. In pre-treatment, the LIB is firstly discharged and disassembled manually. Secondly, the unit cells are shattered and separated into black mass mainly by physical properties through secondary treatment. Lastly, the black mass is decomposed into raw materials for recovery or resynthesizing in further treatment. Interdisciplinary approaches and secondary use feasibility are also discussed for future application prospect.